EARLY VERSUS LATE TRACHEOTOMY IN THE INTENSIVE CARE UNIT - Dimitrov, Ivica; Sazdov, Darko; Shikov, Nikola; Chukalevski, Pande; Georgievska, Natalija Chakar (Journal of Morphological Sciences, 2024)
Prolonged intubation and mechanical ventilation in critically ill patients can lead to several complications such as: Tracheomalacia, tracheoesophageal fistula, pulmonary atelectasis, respiratory infections, which is why tracheotomy is recommended. Also, the purpose of tracheotomy is shortening of the dead space in the airways and easier release (weaning) from mechanical ventilation. To determine the association of early and late tracheotomy with: Total days from tracheotomy to first ventilator weaning, total days of spontaneous breathing-T cannula, Non-invasive ventilation and mechanical ventilation before and after tracheotomy, number of bronchoaspirations, atelectasis and number of respiratory infections (with causative bacteria) before and after tracheotomy, length of hospitalization, death in intensive care and comorbidities. To determine the association of total days from tracheotomy to first ventilator weaning with gender and age of patients and to to determine the percentage of complications in early VS late tracheotomy.  This  comparative study includes 56 patients aged from 18 to 91 years with elective surgical tracheotomy. Patients are divided into 2 groups: 28 patients with early tracheotomy (time from intubation to tracheotomy â‰¤7 days) 28 patients with late tracheotomy (time from intubation to tracheotomy >7 days). The length of hospitalization was significantly longer in the late tracheotomy group (p=0.0013). The number of days of mechanical ventilation before tracheotomy was significantly higher in patients with late tracheotomy (p=0.000001). The mortality rate was significantly higher in the late tracheotomy group (p=0.009). No statistical significance was found between the time from tracheotomy to the first weaning, the number of bronchoaspirations and atelectasis before and after tracheotomy in both groups of patients.    In our study, we determined that patients with late tracheotomy statistically have higher mortality, longer hospitalization and more frequent respiratory infections before tracheotomy compared to patients with early tracheotomy. Keywords: early tracheotomy, late tracheotomy